2015
DOI: 10.3892/etm.2015.2419
|View full text |Cite
|
Sign up to set email alerts
|

Effect of erythropoietin on the expression of dynamin-related protein-1 in rat renal interstitial fibrosis

Abstract: Abstract. This study aimed to observe the expression of dynamin-related protein-1 (Drp-1) in the renal interstitium in a rat model of renal interstitial fibrosis induced by unilateral ureteral obstruction (UUO). In addition, the renoprotective effect of erythropoietin in this model was investigated. A total of 81 rats were randomly assigned to sham surgery, UUO model and treatment groups. Following surgery, the rats in the treatment group were subcutaneously administered erythropoietin at a dose of 3,000 IU/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The current information strongly suggests that bioenergetics impairment triggers several alterations in mitochondrial homeostasis, among which we find: reduction in mitochondrial number and mass and in biogenesis, 33,58 shift of the dynamics towards fission, 90–94 disturbance in mitophagy flux 93,101 and the dysregulation in Ca +2 levels 67,69,70 . Given the close relationship between the ER and mitochondria, in UUO mitochondrial alterations also favor ER impairment, which can be explained by oxidative stress increase, 18,21,39 Ca +2 depletion, 61,67,69,70 and FA accumulation, 33,51 favoring ER stress‐increased cell damage 136,139 .…”
Section: Final Remarks and Future Directionsmentioning
confidence: 70%
See 1 more Smart Citation
“…The current information strongly suggests that bioenergetics impairment triggers several alterations in mitochondrial homeostasis, among which we find: reduction in mitochondrial number and mass and in biogenesis, 33,58 shift of the dynamics towards fission, 90–94 disturbance in mitophagy flux 93,101 and the dysregulation in Ca +2 levels 67,69,70 . Given the close relationship between the ER and mitochondria, in UUO mitochondrial alterations also favor ER impairment, which can be explained by oxidative stress increase, 18,21,39 Ca +2 depletion, 61,67,69,70 and FA accumulation, 33,51 favoring ER stress‐increased cell damage 136,139 .…”
Section: Final Remarks and Future Directionsmentioning
confidence: 70%
“…Additionally, in the renal tubulointerstitium, where Drp1 is normally expressed at low levels, UUO-OKs also show a temporal increase in the expression of Drp1. 94 In the same way, sirtuin 3 (SIRT3) is a deacetylase protein mainly localized in mitochondria, involved in the regulation of mitochondrial biogenesis and dynamics. 95,96 SIRT3 protein levels are decreased in UUO-OKs.…”
Section: Mitochondrial Mass and Dynamics Alterationsmentioning
confidence: 99%
“…The renal protective effect of EPO has been reported in many literatures. Zhao et al [16] found that EPO can improve renal dysfunction and interstitial fibrosis in rats with unilateral ureteral obstruction. Acikgoz' study showed that the antifibrotic effect of EPO on rats with obstructive renal fibrosis may be regulated by nuclear factor kappa B (NF-rB) signaling pathway [17].…”
Section: Discussionmentioning
confidence: 99%
“…Renoprotection is promoted via an anti-apoptotic effect from the expression of the EPO receptor, the reduction of the Bax/Bcl-XL ratio, the inhibition of cytochrome-c release into the cytosol, and the decrease of active caspase-3 expression. EPO treatment also reduces renal fibrosis in UUO model rats, and downregulates Drp1 overexpression to reduce mitochondria fission ( Zhao et al, 2015 ).…”
Section: Drugsmentioning
confidence: 99%